(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
The melting diagram of the B–B2O3–BN ternary system at 5 GPa has been calculated in the framework of phenomenological thermodynamics models. The literature data has been used for the model stability parameters and the unknown interaction parameters of models have been defined from the experimental studies of the phase equilibria. The diagram is characterized by the existence of two eutectic, one peritectic and the maximum in univariant eutectic line invariant equilibria.